2017
DOI: 10.1016/j.surg.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with milk fat globule epidermal growth factor-factor 8 (MFG-E8) reduces inflammation and lung injury in neonatal sepsis

Abstract: Introduction Sepsis remains one of the leading causes of infant death worldwide. It is characterized as uncontrolled inflammatory responses due to proven bacterial infection. Despite improvement in supportive care and the availability of effective antibiotics, no specific therapy targeting the dysregulated inflammatory response is available for neonatal sepsis. Milk fat globule epidermal growth factor-factor 8 (MFG-E8) is a secretory glycoprotein abundantly present in human milk. MFG-E8 suppresses the systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In addition to its protective role in intestinal tissues, MFG-E8 has been shown to regulate osteoclast homeostasis and protect against inflammatory bone loss [ 38 ]. Treatment with MFG-E8 reduces inflammation and lung injury [ 39 ], and MFG-E8/lactadherin was found to enhance neovascularization and promote wound healing [ 17 , 18 ]. In the present study, we found that Mfge8 expression is not only sustained in ductal epithelial cells but activated in acinar cells as well as endothelial cells of interlobular blood vessels during acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its protective role in intestinal tissues, MFG-E8 has been shown to regulate osteoclast homeostasis and protect against inflammatory bone loss [ 38 ]. Treatment with MFG-E8 reduces inflammation and lung injury [ 39 ], and MFG-E8/lactadherin was found to enhance neovascularization and promote wound healing [ 17 , 18 ]. In the present study, we found that Mfge8 expression is not only sustained in ductal epithelial cells but activated in acinar cells as well as endothelial cells of interlobular blood vessels during acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Breast milk contains immunoglobulins, cytokines, lactoferrin, and growth factors (Torrazza and Neu 2013 ). Breast milk also contains glycoproteins that have been shown to decrease organ injury and inflammation in sepsis in mouse models (Hansen et al 2017b ). In addition human milk contains human milk oligosaccharides (HMO) that stimulates the growth of “healthy” bacteria- Bifidobacteria and Bacteroides species both possess the proper enzymes to digest HMOs and metabolize them for energy.…”
Section: Dietary Impact On the Microbiomementioning
confidence: 99%
“…Excessive inflammation and oxidative stress were recognized as the underlying mechanism in cognitive impairments caused by sepsis [22,23]. After that, severe acute kidney injury [24,25], lung injury [26], liver failure [27] as well as cognitive impairments were all detrimental to sepsis patients. Early research reported that BBR combination with yohimbine was helpful in the early phase of sepsis in which drugs were administered 2 h after CLP surgery [15].…”
Section: Researchmentioning
confidence: 99%